2007
DOI: 10.1007/s00466-007-0170-1
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of impact fracture behavior of automobile laminated glass by 3D discrete element method

Abstract: A three-dimensional discrete element model of laminated glass plane is presented and a 3D numerical analysis code, which can simulate the impact fracture behavior of automobile laminated glass, is developed. The impact process of a single glass plane and a laminated glass plane are calculated in the elastic range by the code. Comparing its results with those calculated by the commercial FEM code LS-DYNA in the same condition, the validity of the 3D laminated glass model and the 3D discrete element method are p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(52 citation statements)
references
References 12 publications
(18 reference statements)
1
47
0
Order By: Relevance
“…The glass and PVB of LG planes were discretizing to uniform rigid spherical elements ( Figure 1). This investigation showed that the accuracy of the 3D model and numerical analysis were significantly validated in the elastic range in comparison to FEM [62]. The combined discrete and FE methods overcome the inability of DEM to describe the large deformation behavior of the inter-layer.…”
Section: Literature Reviewmentioning
confidence: 84%
See 1 more Smart Citation
“…The glass and PVB of LG planes were discretizing to uniform rigid spherical elements ( Figure 1). This investigation showed that the accuracy of the 3D model and numerical analysis were significantly validated in the elastic range in comparison to FEM [62]. The combined discrete and FE methods overcome the inability of DEM to describe the large deformation behavior of the inter-layer.…”
Section: Literature Reviewmentioning
confidence: 84%
“…The interactions between DEs are usually handled by using contact algorithms. Zang et al [62] used 3D discrete element method to study the impact fracture of LG. The glass and PVB of LG planes were discretizing to uniform rigid spherical elements ( Figure 1).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the same year, Zang and Wang dealt with the impact behavior on glass panels in the automotive sector [11]. In doing so, self-developed methods of numerical simulation were supposed to be compared with commercial codes.…”
Section: State-of-the-artmentioning
confidence: 99%
“…Zang et al [14] also investigated on impact fracture behavior of automobile laminated glass by 3D discrete element method. The authors' investigation focused on the use of the 3D discrete element method to study the impact fracture problem of laminated glass.…”
Section: Introductionmentioning
confidence: 99%